Pharmacological properties of TRPM3 isoforms are determined by the length of the pore loop. (28th August 2020) - Held, Katharina; Aloi, Vincenzo Davide; Freitas, Ana Cristina Nogueira; Janssens, Annelies; Segal, Andrei; Przibilla, Julia; Philipp, Stephan Ernst; Wang, Yu Tian; Voets, Thomas; Vriens, Joris
Abstract : Background and Purpose: Transient receptor potential melastatin 3 (TRPM3) is a non‐selective cation channel that plays a pivotal role in the peripheral nervous system as a transducer of painful heat signals. Alternative splicing gives rise to several TRPM3 variants. The functional consequences of these splice isoforms are poorly understood. Here, the pharmacological properties of TRPM3 variants arising from alternative splicing in the pore‐forming region were compared. Experimental Approach: Calcium microfluorimetry and patch clamp recordings were used to compare the properties of heterologously expressed TRPM3α1 (long pore variant) and TRPM3α2–α6 (short pore variants). Furthermore, site‐directed mutagenesis was done to investigate the influence of the length of the pore loop on the channel function. Key Results: All short pore loop TRPM3α variants (TRPM3α2–α6) were activated by the neurosteroid pregnenolone sulphate (PS) and by nifedipine, whereas the long pore loop variant TRPM3α1 was insensitive to either compound. In contrast, TRPM3α1 was robustly activated by clotrimazole, a compound that does not directly activate the short pore variants but potentiates their responses to PS. Clotrimazole‐activated TRPM3α1 currents were largely insensitive to established TRPM3α2 antagonists and were only partially inhibited upon activation of the μ opioid receptor. Finally, by creating a set of mutant channels with pore loops of intermediate length, we showed that the length of the pore loop dictates differential channel activation by PS and clotrimazole. Conclusion and Implications: Alternative splicing in the pore‐forming region of TRPM3 defines the channel's pharmacological properties, which depend critically on the length of the pore‐forming loop. LINKED ARTICLES: This article is part of a themed issue on Structure Guided Pharmacology of Membrane Proteins (BJP 75th Anniversary). To view the other articles in this section visit http://onlinelibrary.wiley.com/doi/10.1111/bph.v179.14/issuetoc